ANALISIS EFISIENSI PENGGUNAAN MODAL KERJA PADA KOPERASI UNIT DESA (KUD) TANI BAHAGIA DESA KULIM JAYA KECAMATAN LUBUK BATU JAYA KABUPATEN INDRAGIRI HULU TAHUN 2012-2016 - Lestari, Tuti Indra; Caska, Caska; Hendripides, Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims to analyze the Efficiency of Capital usage on Tani Bahagia Coorperative Village Unit, Kulim Jaya Village, Indragiri Hulu District. This research uses secondary data in form financial statements from balance sheet, calculation of business of result, and change capital statements of Tani Bahagia Cooperative Village Unit, Kulim Jaya Village, Indragiri Hulu District year 2012-2016. This research applies descriptive analysis by using financial statements of the cooperative. Afterward, the result would be adjusted with the standard of criterion of working capital tunrnover and efficiency measurement also added from the from the aspect of rentability own capital. The research result showed that working capital efficiency rate of Tani Bahagia Coorperative Village Unit, Kulim Jaya Village, Indrgiri Hulu District year 2012 – 2016 seen from working capital turnover always encounter fluctuation (changes) that proves capital rentability rate is less efficient. It can be concluded that working capital has possitive impact on rentability own capital.Keywords: Working Capital Efficiency and Rentability Own Capital